INTEGRATION OF NATURAL SCIENCE ACHIEVEMENTS IN MEDICAL EDUCATION: NEW APPROACHES AND TECHNOLOGIES (Uzbekistan Open Conference, 2025)
The article discusses modern ways of combining the achievements of natural sciences with medical education. The main focus is on the use of new technologies - virtual and augmented reality (VR/AR), artificial intelligence, telemedicine and digital platforms. It is shown that the combination of biology, physics, chemistry and computer science helps to prepare future doctors for practical work. The directions of the development of digital medical education and the role of natural sciences in the training of new generation specialists have been identified.